"Breek die tempel af": Etiese dimensies in Johannes 2:13-22? - Watt, Jan Gabriël van der (HTS teologiese studies, 2015)
Destroy this temple’: Ethical dimensions in John 2:13–22? The question asked is to what extent could one speak of ethical dynamics in the Gospel of John, even in cases where there is no surface level textual evidence for the presence of ethical material? It is argued that through the process of rereading (‘relecture’), which is invited by the Johannine text as performative text, ethical dimensions are highlighted in texts where such emphases were not apparent at the first reading. As example the events at the temple, narrated in John 2:13–22, are analysed.